MENTORING THROUGH LESSON STUDY: A COLLABORATIVE WAY TO SUPPORT EFL TEACHERS’ PROFESSIONAL DEVELOPMENT IN MADRASAHS (ISLAMIC SCHOOLS) - Ekawati, Dian; Damayanti, Ika Lestari; Lengkanawati, Nenden Sri (International Journal of Education, 2022)
Recently, attending seminars or professional development programs for teachers is not sufficient to cope with today's teaching challenges. In addition, tight schedules and preparing teaching administration often refrain teachers to work and discuss together with their colleagues. Pointing out such problems, this study tries to investigate how mentoring program for EFL teachers in Indonesia was conducted collaboratively at schools through a lesson study approach and what teachers’ competencies were improved during the program. Eight EFL teachers from three Islamic junior high schools (called madrasahs) and a university lecturer serving as a mentor were involved in the program. Data gathered from observations, questionnaires, and interviews were analyzed qualitatively through (1) iterative reading of the data, (2) reducing the data, (3) categorizing the data, (4) combining all data, and (5) concluding the data.  The findings indicate that the lesson study cycle involved in this program covered two stages of PLAN, one stage of DO, and SEE. The participant teachers required more time during the planning due to several factors such as adjustment working with the revised Curriculum recently released by the government at the time of data collection, and challenges in aligning learning objectives, classroom activities, and evaluation. Upon their involvement in the program, the teachers reported that they gained benefits and strong improvements in four aspects of teachers' competencies, namely professional, pedagogical, social, and personal competencies from the collaboration with peer teachers and a university lecturer. For instance, they found their knowledge extending in terms of teaching techniques and methods, planning and implementing effective lessons, and their motivation to teach better and share resources with others increasing as well. In short, mentoring through lesson study is valuable to improve the teachers’ competencies.